2012
DOI: 10.5923/j.als.20120202.04
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties of <i>Thuja Orientalis</i> Linn

Abstract: Thuja orientalis (Commonly-Morpankhi, Family-Cupressaceae) is an evergreen, monoecious trees or shrubs used in various forms of traditional medicines and homeopathy in various ways. In traditional practices Thuja is used for treatment of bronchial catarrh, enuresis, cystitis, psoriasis, uterine carcinomas, amenorrhea and rheumatism. Recent researches in different parts of the world have shown that T. orientalis and its active component thujone have the great potential against a various health problems. T. orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…It is interesting to note that these strains are responsible for various plant diseases like crown gall, leaf blight, leaf spot and rot disease; therefore the present findings would be useful in curing various human and plant bacterial disease. Recently, Srivastava et al (2012), reviewed biological properties of B. orientalis and concluded that it has the great potentiality against a number of health problems namely: bacterial, fungal and worm infections. Relying upon the present findings it is clear that all extracts had very promising results against the tested bacterial pathogenic strains in comparison to synthetic drugs Ampicillin and Erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that these strains are responsible for various plant diseases like crown gall, leaf blight, leaf spot and rot disease; therefore the present findings would be useful in curing various human and plant bacterial disease. Recently, Srivastava et al (2012), reviewed biological properties of B. orientalis and concluded that it has the great potentiality against a number of health problems namely: bacterial, fungal and worm infections. Relying upon the present findings it is clear that all extracts had very promising results against the tested bacterial pathogenic strains in comparison to synthetic drugs Ampicillin and Erythromycin.…”
Section: Discussionmentioning
confidence: 99%
“…1). Herein we report the isolation and structural elucidation of isolates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) propane ring in the molecule [11]. The 13 C NMR spectrum (l " Table 1) in combination with DEPT showed four tertiary methyls, three methines, four methylenes including a characteristic signal for the cyclopropane ring at δ C 10.9 [11], four quaternary carbons, and one methoxy carbon signals.…”
mentioning
confidence: 94%
“…The full assignments of 1 H and 13 C NMR chemical shifts for thujopsadiene (4) were obtained by 2D-NMR for the first time. All compounds (1-11) showed antiproliferative activities against the SK-OV-3 and SK-MEL-2 cell lines with IC 50 values of 5. compounds 1,3,4,7,8, and 9 significantly inhibited nitric oxide production in lipopolysaccharide-activated BV-2 cells with IC 50 values of 3.93-17.85 µM without cell toxicity. …”
mentioning
confidence: 95%
See 2 more Smart Citations